A scoping review on interpersonal coping in sports - Eckardt, V. C.; Tamminen, K. A. (International Review of Sport and Exercise Psychology, 2025)
Social relationships become crucial in times of stress and adversity. While research on interpersonal coping has acknowledged human interdependency and is gaining momentum in sport psychology, a lack of conceptual clarity and divergence in nomenclature is currently hindering the field to move forward. Thus, the aim of this scoping review was to map the current evidence on contextual characteristics, antecedents, strategies, and outcomes of interpersonal coping (i.e. communal coping, dyadic coping) in sports. Six databases were systematically searched utilizing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist. Eleven studies were included in the current review and subject to data extraction and quality assessment. Data were charted according to the PRISMA extension checklist for Scoping reviews (PRISMA-ScR). Findings show that communal coping has primarily served to investigate joint coping efforts of teams or families during significant events or transitions, while dyadic coping sheds light on stressor management between athletes, or athletes and their coaches. Further, most studies were theory-driven and employed a qualitative methodology with a cross-sectional study design. Multi-group sampling was largely neglected. We conclude by explicating research gaps based on the populations and topics studied as well as the methodologies used to propose fruitful avenues for future research.